Development of a conceptual framework for understanding financial barriers to care among patients with cardiovascular-related chronic disease: a protocol for a qualitative (grounded theory) study - Campbell, David J.T. (CMAJ Open, 2016)
BACKGROUND: Patients with cardiovascular-related chronic diseases may face financial barriers to accessing health care, even in Canada, where universal health care insurance is in place. No current theory or framework is adequate for understanding the impact of financial barriers to care on these patients or how they experience financial barriers. The overall objective of this study is to develop a framework for understanding the role of financial barriers to care in the lives of patients with cardiovascular-related chronic diseases and the impact of such barriers on their health. METHODS: We will perform an inductive qualitative grounded theory study to develop a framework to understand the effect of financial barriers to care on patients with cardiovascular-related chronic diseases. We will use semistructured interviews (face-to-face and telephone) with a purposive sample of adult patients from Alberta with at least 1 of hypertension, diabetes, heart disease or stroke. We will analyze interview transcripts in triplicate using grounded theory coding techniques, including open, focused and axial coding, following the principle of constant comparison. Interviews and analysis will be done iteratively to theoretical saturation. Member checking will be used to enhance rigour. INTERPRETATION: A comprehensive framework for understanding financial barriers to accessing health care is instrumental for both researchers and clinicians who care for patients with chronic diseases. Such a framework would enable a better understanding of patient behaviour and nonadherence to recommended medical therapies and lifestyle modifications.